2011
DOI: 10.3892/or.2011.1569
|View full text |Cite
|
Sign up to set email alerts
|

Koetjapic acid, a natural triterpenoid, induces apoptosis in colon cancer cells

Abstract: Abstract. Deregulated cell signaling pathways result in cancer development. More than one signal transduction pathway is involved in colorectal cancer pathogenesis and progression. Koetjapic acid (KA) is a naturally occurring seco-A-ring oleanene triterpene isolated from the Sandoricum koetjape stem bark. We report the cellular and molecular mechanisms of anticancer activity of KA towards human colorectal cancer. The results showed that KA induces apoptosis in HCT 116 colorectal carcinoma cells by inducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Apoptotic cells undergo a series of characteristic morphological and biochemical changes, which usually manifest themselves as nuclear condensation, DNA fragmentation, and chromatin dissolution [13]. In this study, Hoechst-stained images of B2-treated PC3 cells revealed clear proapoptotic signs such as chromatin condensation and dissolution.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Apoptotic cells undergo a series of characteristic morphological and biochemical changes, which usually manifest themselves as nuclear condensation, DNA fragmentation, and chromatin dissolution [13]. In this study, Hoechst-stained images of B2-treated PC3 cells revealed clear proapoptotic signs such as chromatin condensation and dissolution.…”
Section: Discussionmentioning
confidence: 51%
“…Effect of B2 on nuclear chromatin condensation in PC3 cells was quantified by fluorescence microscopy using Hoechst 33258 stain [13]. …”
Section: Methodsmentioning
confidence: 99%
“…It is not known which of the compounds present in the active fraction of B. albiflora may cause activation of the extrinsic pathway of apoptosis. Regardlessly, there are reports of the induction of apoptosis by activation of extrinsic signaling mediated by natural and synthetic triterpenoids [4648]. Additionally, the lanostane-type triterpenoid, polyporenic acid C isolated from Poriacocos , induces caspase-8-mediated apoptosis in human lung cancer [49].…”
Section: Resultsmentioning
confidence: 99%
“…Effect of SSG on nuclear chromatin condensation in PC3, MCF7 and HCT 116 cells was quantified by fluorescence microscopy using Hoechst 33258 stain [51]. Cells were treated with SSG (10 µM) and analysed separately at two different time intervals (6 and 18 hr).…”
Section: Methodsmentioning
confidence: 99%